(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Abrus precatorius Linn is traditionally celebrated for its diverse pharmacological benefits, yet comprehensive studies correlating its leaf phytoconstituents with anti-colorectal cancer potential remain limited. This study presents an integrated approach evaluating the phytochemical profile, in silico molecular docking, and in vitro cytotoxicity of the ethanolic leaf extract of A. precatorius against HCT116 human colorectal carcinoma cells. Shade- dried leaves were extracted via Soxhlet extraction using ethanol. The extract underwent preliminary qualitative screening and Gas Chromatography-Mass Spectrometry (GC-MS) profiling. Molecular docking via the Swiss Dock platform was utilized to predict binding interactions against cancer-associated proteins, including PI3K-α and PRKAG1. In vitro antiproliferative activity against HCT116 cells was determined using the MTT cell viability assay across concentrations ranging from 10 to 100 μg/mL. Qualitative screening confirmed the presence of alkaloids, flavonoids, tannins, saponins, glycosides, and steroids/triterpenoids. GC-MS analysis resolved over 140 chromatographic peaks, prominently featuring 4-O-Methyl-D-arabinose/Mome inositol (17.45%). In silico docking revealed that 5′- adenylic acid possessed the strongest binding affinity (-5.427 kcal/mol) toward PRKAG1, indicating potential downstream mTOR signaling suppression. The MTT assay demonstrated a clear dose-dependent inhibition of HCT116 cells, reaching 80.60% inhibition at 100 μg/mL and yielding a moderate IC50 value of 46.32 μg/mL. This integrated phytochemical, computational, and biological evaluation scientifically substantiates the anti-colorectal cancer potential of A. precatorius leaves. The observed cytotoxic activity warrants further chromatographic isolation of bioactive molecules and detailed downstream apoptotic mechanistic investigations.